Draft Annual Plan 2008-2009 Government of Mizoram - Planning Commission (Planning Commission, 2008)
Mizoram is bounded on the north by the States of Assam and Manipur, on the east and south by Chin Hills of Myanmar, and on the west by Chittagong Hill tracts of Bangladesh and the state of Tripura. It is a hilly terrain covering an area of 21,087 sq.km and enjoys a cool temperate climate. The average annual rainfall is around 217.5cm and temperature varies between 12° and 18° Celsius in winter and 18° and 29° Celsius in summer.
Government of Mizoram, Planning and Programme Implementation Department